The Use of Comic to Improve Students’ Reading Comprehension Skill at Junior High School - Afwun Kamil; Endang Komariah; Yuliana Natsir (Research in English and Education Journal, 2017)
The objective of this experimental study is to know the achievement of students reading comprehension after implementing comic as learning media. The population was all of the eighth grade students of SMPN 17 Banda Aceh. The sample was the students of class VIII-9 (experimental class) and VIII-6 (control class). True Exprimental Design is used in this study. The writer conducted pre-test, treatment and post-test to collect data, and used gain score calculation. The mean score of pre-test in experimental class was 62 and post-test was 75.6, while the mean score of pre-test in control class was 36.8, and post-test was 59.2. The gain score of experimental class was 9.78, while control class was 8.11. It indicated that there was an improvement of students’ achievement both of classes. However, the improvement of students’ achievement in experimental class is higher than control class. Moreover, the analysis of t-test showed that tscore ttable or 2.36 1.68 at the level of significance 0.05 with the degree of freedom (df) 25. It is clear that the alternative hypothesis (Ha) is accepted. It means that comic is effective media in teaching learning reading recount text.